Um estudo sobre o perfil do investidor de fundos de investimento imobiliário e a relação entre os indicadores IFIX, IBOV e CDI. - Nogueira, Bruna Rocha (Universidade Federal de São Carlos, 2021)
The present work aims to map the profile of the investor of Real Estate Investment Funds in Brazil, based on the analysis of responses collected in a market survey and also to conclude the list of indicators of the São Paulo Stock Exchange Index (IBOV) and Credit of Interbank Deposit (CDI) before the Real Estate Investment Funds Index (iFIX), using the Multiple Linear Regression algebraic method. In this context, the study proves the greater sensitivity of iFIX linked to the IBOV, characterizing the asset within variable income products, which are adequate and generally present in the portfolio of investors with a moderate profile.
A study on the investor profile of real estate investment funds and the relationship between IFIX, IBOV and CDI INDICATORS.
Keywords: Fundos de Investimento Imobiliário; fundos; imobiliário; investimentos; mercado e FIIs.; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA::ESTUDO DE MERCADO